2022
DOI: 10.7554/elife.74509
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic reconstruction of the hunchback promoter specifies the role of Bicoid, Zelda and Hunchback in the dynamics of its transcription

Abstract: For over 40 years, the Bicoid-hunchback (Bcd-hb) system in the fruit fly embryo has been used as a model to study how positional information in morphogen concentration gradients is robustly translated into step-like responses. A body of quantitative comparisons between theory and experiment have since questioned the initial paradigm that the sharp hb transcription pattern emerges solely from diffusive biochemical interactions between the Bicoid transcription factor and the gene promoter region. Several alterna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…To circumvent this problem, the idea of spatial averaging by the nuclei was introduced in order to increase the precision to the desired level [13]. Over the years the mechanism of Gregor et al has been widely applied [13][14][15][16][17][18][19] but the problem of interpretation of BCD gradient by its primary target gene hb still remains poorly understood [19][20][21][22][23][24][25]. In fact a recent theoretical analysis has shown that spatial averaging is a priori dispensable but the treatment given is unwieldy and introduces another adhoc hypothesis of dynamically changing time windows [23].…”
Section: (E) Precise Interpretation Of the Bcd Morphogenmentioning
confidence: 99%
See 2 more Smart Citations
“…To circumvent this problem, the idea of spatial averaging by the nuclei was introduced in order to increase the precision to the desired level [13]. Over the years the mechanism of Gregor et al has been widely applied [13][14][15][16][17][18][19] but the problem of interpretation of BCD gradient by its primary target gene hb still remains poorly understood [19][20][21][22][23][24][25]. In fact a recent theoretical analysis has shown that spatial averaging is a priori dispensable but the treatment given is unwieldy and introduces another adhoc hypothesis of dynamically changing time windows [23].…”
Section: (E) Precise Interpretation Of the Bcd Morphogenmentioning
confidence: 99%
“…Theories employing detailed balance arguments have also not proven much helpful in this regard [22]. Recent theoretical treatments invoking hypotheses like dynamically changing time windows predict an interpretation time of less than a minute and remain unsubstantiated in vivo [9,[23][24][25]. However, experimentally BCD is known to bind to chromatin sites in a highly transient manner, with specific binding events lasting on the order of a second, in all portions of the embryo [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling how repressors specify the edge of Ftz stripes may provide a unique opportunity to extend the well-developed theoretical frameworks that connect enhancer sequence to boundary specification by activator proteins. The best-known examples of such studies are predictions for how the Bicoid activator gradient specifies the Hunchback boundary [38][39][40][41][42] . Compared to Hunchback, the Ftz boundaries are specified much faster and are much sharper, which will pose new challenges to existing models that would likely yield fundamentally new insights.…”
Section: )mentioning
confidence: 99%
“…The resulting bcd mutant faithfully recapitulated the appearance of the strongest bcd alleles (Huang et al, 2017). In a recent study (Fernandes et al, 2022), a complete removal of the bcd locus based on CRISPR technology was achieved. However, no in-depth analysis was conducted using this allele.…”
Section: Introductionmentioning
confidence: 99%